2013
DOI: 10.1371/journal.pone.0054794
|View full text |Cite
|
Sign up to set email alerts
|

Integrity and Regeneration of Mechanotransduction Machinery Regulate Aminoglycoside Entry and Sensory Cell Death

Abstract: Sound perception requires functional hair cell mechanotransduction (MET) machinery, including the MET channels and tip-link proteins. Prior work showed that uptake of ototoxic aminoglycosides (AG) into hair cells requires functional MET channels. In this study, we examined whether tip-link proteins, including Cadherin 23 (Cdh23), regulate AG entry into hair cells. Using time-lapse microscopy on cochlear explants, we found rapid uptake of gentamicin-conjugated Texas Red (GTTR) into hair cells from three-day-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 46 publications
(101 reference statements)
0
57
0
Order By: Relevance
“…For hair cells counting, we used the cell counter tool in Image J software to accumulate the myosinVIIa-positive hair cells within the 400 μm length in the middle turn of the cochlea [17]. As for the quantification of fluorescence intensity of prestin, we also performed as previous study [17].…”
Section: Methodsmentioning
confidence: 99%
“…For hair cells counting, we used the cell counter tool in Image J software to accumulate the myosinVIIa-positive hair cells within the 400 μm length in the middle turn of the cochlea [17]. As for the quantification of fluorescence intensity of prestin, we also performed as previous study [17].…”
Section: Methodsmentioning
confidence: 99%
“…Unlike most cells, sensory hair cells have mechano-electrical transduction (MET) channels that are uniquely gated by tip links between individual stereocilia in their apically-located hair bundle (Assad et al, 1991; Hudspeth, 1986; Hudspeth and Corey, 1977; Pickles et al, 1984). Data from electrophysiological and time-lapse imaging studies, as well as drug uptake studies in hair cells with dysfunctional MET channels strongly suggest that the ototoxic aminoglycosides (molecular diameter ~0.81 nm; molecular mass ~445–477 for gentamicin) can permeate through the MET channel pore of at least 1.25 nm (Alharazneh et al, 2011; Farris et al, 2004; Marcotti et al, 2005; Vu et al, 2013). A recent study demonstrated that functional MET channels are required for cytosolic uptake of fluorescently-tagged cisplatin, and for cisplatin-induced hair cell death (Thomas et al, 2013).…”
Section: Cisplatin and Other Platinum Compoundsmentioning
confidence: 99%
“…Hair cells have a mechanosensory hair bundle located at their apical surface, and there is evidence that the aminoglycosides, known to be permeant blockers of the mechanoelectrical transducer (MET) channels in the hair bundle, enter into hair cells via these large-conductance cation channels (10)(11)(12)(13)(14). Once inside the hair cell, the aminoglycosides cause increases in reactive free radicals and mitochondrial calcium concentration, leading to either apoptosis or necrosis (1,2,15).…”
Section: Introductionmentioning
confidence: 99%